2022
DOI: 10.3390/mi13010093
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Culture Chip with Transparent, Micropillar-Decorated Bottom for Live Cell Imaging and Screening of Breast Cancer Cells

Abstract: In the recent years, microfabrication technologies have been widely used in cell biology, tissue engineering, and regenerative medicine studies. Today, the implementation of microfabricated devices in cancer research is frequent and advantageous because it enables the study of cancer cells in controlled microenvironments provided by the microchips. Breast cancer is one of the most common cancers in women, and the way breast cancer cells interact with their physical microenvironment is still under investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…59−61 Cell nuclei undergo severe deformation on micropillar arrays with an appropriate dimension, which influenced cell behaviors. 62 Nuclear deformation can also cause chromatin condensation and chromosome relocalization within the nucleus and alter gene expression of the cells. 63−66 It has been demonstrated that actomyosin and microtubule may synergistically regulate nuclear deformation and chromatin remodeling, finally modulating gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59−61 Cell nuclei undergo severe deformation on micropillar arrays with an appropriate dimension, which influenced cell behaviors. 62 Nuclear deformation can also cause chromatin condensation and chromosome relocalization within the nucleus and alter gene expression of the cells. 63−66 It has been demonstrated that actomyosin and microtubule may synergistically regulate nuclear deformation and chromatin remodeling, finally modulating gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between cells and materials is a fundamental issue in the fields of biomaterials and tissue regeneration. Micropillar arrays provide a unique kind of topological surfaces to regulate cell-material interactions. Cell nuclei undergo severe deformation on micropillar arrays with an appropriate dimension, which influenced cell behaviors . Nuclear deformation can also cause chromatin condensation and chromosome relocalization within the nucleus and alter gene expression of the cells. It has been demonstrated that actomyosin and microtubule may synergistically regulate nuclear deformation and chromatin remodeling, finally modulating gene expression .…”
Section: Discussionmentioning
confidence: 99%
“…Nanotechnology, operating at an atomic and molecular scale, represents the fourth industrial revolution, profoundly influencing contemporary society [1]. In the realm of nanotechnology, microfabrication plays a pivotal role not only in manufacturing integrated circuits for the semiconductor industry but also in various domains, such as electronics, micro electromechanical systems (MEMS) devices, microfluidics, cell culture, and regenerative medicine in tissue engineering [2][3][4]. Focusing on applications in the biological domain, micro-and nanofabrication techniques hold immense potential for tailoring biomaterials with desired characteristics [5,6].…”
Section: Introductionmentioning
confidence: 99%